Analisis Kesehatan Bank Umum Syariah di Indonesia Menggunakan Metode RBBR Tahun 2021-2024 - Arisha Putri Pradita; Vika Diyah Ardiyanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the health of Islamic Commercial Banks in Indonesia using four indicators of the Risk-Based Bank Rating (RBBR) method: risk profile (NPF), profitability (ROA), capital (CAR), and good corporate governance (GCG) from 2021 to 2024. A descriptive research approach was employed, utilizing secondary data obtained from the Islamic Banking Statistics reports published by the Financial Services Authority (OJK). Data analysis was conducted by presenting tables and identifying performance trends in each of the main RBBR indicators, namely risk profile (NPF), profitability (ROA), capital (CAR), and good corporate governance (GCG). The results of the study indicate that Islamic Commercial Banks in Indonesia have demonstrated a positive trend across all indicators. The risk profile indicator, represented by Non-Performing Financing (NPF), showed a decline from 2.59% in 2021 to 2.08% in 2024, placing Islamic Commercial Banks in the